2021
DOI: 10.3390/molecules26144326
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids Isolated from Podocarpus macrophyllus Inhibited the Inflammatory Mediators in LPS-Induced HT-29 and RAW 264.7 Cells

Abstract: Species of Podocarpus are used traditionally in their native areas for the treatment of fevers, asthma, coughs, cholera, chest pain, arthritis, rheumatism, and sexually transmitted diseases. To identify natural products having efficacy against inflammatory bowel disease (IBD), we identified a new, 16-hydroxy-4β-carboxy-O-β-D-glucopyranosyl-19-nor-totarol (4) together with three known diterpenoids from P. macrophyllus. Furthermore, all the extracts, fractions, and isolates 1-4 were investigated for their anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our results, in line with the findings described by other authors, showed that HT-29 cells, subjected to LPS stimuli, release in vitro inflammatory cytokines, including IL-8, TNF-α, and IL-6 [ 47 , 48 ]. The anti-inflammatory activity of PD was evaluated by pretreating or treating HT-29 cells in combination with LPS.…”
Section: Discussionsupporting
confidence: 93%
“…Our results, in line with the findings described by other authors, showed that HT-29 cells, subjected to LPS stimuli, release in vitro inflammatory cytokines, including IL-8, TNF-α, and IL-6 [ 47 , 48 ]. The anti-inflammatory activity of PD was evaluated by pretreating or treating HT-29 cells in combination with LPS.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have found that CASP activation can be observed in tumor cell apoptosis. CASP refers to a family of cysteine aspartate-specific proteases, and these proteases are the main enzymes that perform cell apoptosis and are involved in the occurrence and development of various diseases, particularly tumors and autoimmune diseases[ 26 ]. As a key protease, CASP8 participates in the transmission of exogenous apoptosis signals in mammals, and CASP9 plays a crucial role in the mitochondria-mediated endogenous apoptosis pathway[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equal volumes of both supernatant and Griess reagent were mixed in a dark condition at room temperature for 10 min. Nitric oxide concentration was detected by measuring the absorbance of mixture at 540 nm using an ELISA plate reader (aBMGLABTECH's FLUOstar Omega microplate reader (Ortenberg, Germany), and the percentage of inhibition was calculated based on the following equation (Kim et al, 2021;Ahmed et al, 2022): Inhibition (%) = (absorbance of control cellsabsorbance of sample) x 100/absorbance of control.…”
Section: C) Measurement Of Nitric Oxidementioning
confidence: 99%